2011
DOI: 10.1016/j.jelekin.2010.12.008
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of training intensity between whole-body vibration and conventional squat exercise

Abstract: The aim of this study was to investigate surface electromyographic activity (sEMG) and rate of perceived exertion (RPE) during semi-squat exercise on vibration platform compared with semi-squat exercise performed on a Smith machine. Twenty-three recreationally active students (15 males and 8 females) were exposed to six different loads in one of both exercise modes: vibration or Smith machine. The subject performed a squat in six experimental conditions; the load differed per experimental condition. For each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
(31 reference statements)
2
20
0
1
Order By: Relevance
“…In contrast, there are studies that reported potential benefits of the vibration training for athletes (Delecluse et al, 2005;Marín et al, 2011;Stewart et al, 2009). Those benefits are related among others to the increase in muscular strength, elasticity, and bone density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, there are studies that reported potential benefits of the vibration training for athletes (Delecluse et al, 2005;Marín et al, 2011;Stewart et al, 2009). Those benefits are related among others to the increase in muscular strength, elasticity, and bone density.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have assessed the influence of this kind of training on muscle strength (Delecluse, Roelants, Diels, Koninckx, & Verschueren, 2005;Marín, Santos-Lozano, Santin-Medeiros, Delecluse, & Garatachea, 2011;Stewart, Cochrane, & Morton, 2009), muscle power (Colson & Petit, 2013), muscle stiffness (Colson & Petit, 2013), muscle speed (Delecluse et al, 2005), and jump performance (Lamont et al, 2008). These studies take into account the duration of the training (Stewart et al, 2009) and characteristics of vibration exposure such as frequency and amplitude (Colson & Petit, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst this was not directly quantified in the current study, Pel et al [20] reported a 10-fold reduction in transmission of WBV-induced acceleration from the ankle to the knee/hip at a range of frequencies above 20 Hz. Additionally, a recent study investigating the effects of WBV and conventional loaded squat exercises on muscle activation showed no differences in sEMG at various sites of the body, across a number of training loads and vibratory accelerations [21]. Furthermore, it has been speculated that high muscle activity levels associated with muscle stiffness is a possible explanation for modulation of strength development following WBV exposure [20].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, patients' blood values, i.e., platelets counts, and well-being limit the intensity and volume of resistance training [25,26]. Therefore, whole body vibration (WBV) presents a gentler resistance training method, as it does not additionally exacerbate cardiovascular stress while exercising [27], and reveals similar EMG activity as resistance exercises with external loads [28]. WBV is applied through a vibration platform upon which the subjects stand; it produces alternating sinusoidal movements of the lower body [29].…”
Section: Considering That Muscular Capacity Is One Predictor Formentioning
confidence: 99%